PENGARUH RETURN ON ASSETS DAN RETURN ON EQUITY TERHADAP PRICE TO BOOK VALUE PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Jufri Sani Akbar (JEM Jurnal Ekonomi dan Manajemen, 2021)
Price to Book Value Ratio (PBV) is a ratio that shows the results of the comparison between the market price per share and the book value per share. This ratio is used to measure the level of stock prices whether overvalued or undervalued. The lower the Price to Book Value of stock, the stock is categorized as undervalued, which is very good for long-term investment. However, the low price to book value can also indicate a decline in the quality and fundamental performance of the issuer. The theory that underlies this research is Signaling Theory, which is an action taken by the company to provide instructions for investors about how management views the company's prospects. This signal is in the form of information about what management has done to realize the owner's wishes. This study is to determine the effect of Return on Assets and Return on Equity on Price to Book Value simultaneously and partially in banking companies listed on the Indonesia Stock Exchange. The method used in this study is an associative approach, and the data used are 2020 data with a large sample of 39 banking companies listed on the Indonesia Stock Exchange. The results of this study indicate that there is an effect of Return on Assets and Return on Equity on Price to Book Value simultaneously, there is a partial effect of Return on Assets on Price to Book Value and there is no effect of Return on Equity on Price to Value partially. Keywords: Return on Assets, Return on Equity Price to Book Value.